Polska z bliska - Nowak, Jan, 1913- (Krakow : Wydawn. Znak, 2003)
The author's personal reflections on Polish history and politics since the end of World War II.
Keywords: Poland -- History -- 1945-; Poland -- Politics and government -- 20th century